COMMON WARE WITH ICONOGRAPHICAL MOTIFS FROM VINDOBONA (PANNONIA) - Chinelli, Rita (Rei Cretariae Romanae Fautorum Acta, 2022)
The paper presents some pottery with mythological decoration, made with different techniques. A few of them are local tools or wasters, consequently giving new information about common ware production in Vindobona. The items have been found mostly on the limes road, crossing the canabae legionis and the civilian settlement. The relief and engraved representations belong to the mythological sphere, but the find sites – if known – suggest in primis a profane context. The profane meaning could also have other inbuilt value, now difficult to identify in all the items, but hopefully recognizable after the full interpretation of some new excavations. For this purpose, an attempt was made to connect the finds with the finds sites, despite the difficulties in the majority of cases: in one there is a production framework, in others the excavations are too old to be well documented. However, the aim of the paper is to focus on selected issues, summing up and updating already published finds and commenting on some important aspects of the new ones. This will be a necessary starting point for future in-depth analysis, not least for the integration with the data coming from the project on the stone finds of Vindobona.